(untitled) (Experimental biology, 2026)
The steppe ecosystems of the Akmola Region are a critically important component of the regional carbon cycle, serving as a significant reservoir of organic carbon. However, their carbon sequestration capacity is subject to significant fluctuations depending on vegetation type and climatic conditions. The aim of this study was to conduct a comprehensive quantitative assessment of the main components of the carbon balance based on an analysis of biological productivity - net primary production (NPP) and heterotrophic respiration (Rh). Fieldwork was conducted during the 2025 growing season at 25 permanent monitoring sites in five administrative districts (Egindykol, Akkol, Erementau, Esil, and Atbasar). The methodology was based on A.A. Titlyanova’s “minimum estimates” method, which involves monthly accounting of aboveground and belowground biomass fractions. It was established that productivity processes are characterized by high spatial heterogeneity: maximum productivity was recorded in the mesophytic communities of the Esil District. Under arid conditions (Atbasar District), an adaptive strategy was identified in which the majority of carbon is stored in the roots. The results confirm that during the wet spring of 2025, all studied ecosystems acted as carbon sinks, sequestering between 1.65 and 6.42 t CO₂-eq/ha/year. The study highlights the need to account for root production in climate modeling.